Makna Salat dalam Suluk Saking Kitab Markun Karangan kyai Tumenggung Arungbinang - Umi Masrifah (Analisa: Journal of Social Science and Religion, 2009)
Conduct to Markun book a Kyai Tumenggung Arungbinang essayexplaining the problem of prayers. Prayer is an act that begins withtakbiratul ikhram, ushalli intend to read, read the letter al-Fatikhah, bow,i’tidal, prostrate and tahiyat and ends with a greeting. Conduct of BookMarkun gives specifc meaning to the “members” in the prayer. TakbiratulIkhram (standing) meant as a reminder that everything comes from nothinginto existence. When lafad Allahu Akbar read is to strengthen your heart(those who perform their prayers) to Allah who has created the Great fromnothing into existence.Intention is the lust of the prayers, because if the intention was not dueto glorify God Almighty could make you disbelievers. The Spell of ushalliis not the intention, because the main intention is an intention where thereis no difference between the position and Kawulo Gusti. If God has loved aservant, then all requests will be granted.Surat al-Fatihah is a spirit of prayer, because the letter al-Fatihah is heartof Al-Quran and Al-Fatihah heart is in his heart of Bismillah and the heart ofBismillah is the letter Alif. Bow down to the bone prayer. Bow is not just bow,but humbles them before God Almighty that the actual bow. I’tidal a bodyprayer, while prayer tahiyyat be hand foot and will be praying. Tahiyyatreal meaning is not worship besides Him, have no desire other than to Him.Keywords: Prayer, Book of Conduct of Markun, Kyai TumenggungArungbinang.